Weaving Vocabularies and Counterpoint in Canadian Curriculum Studies - Sameshima, Pauline (Journal of the Canadian Association for Curriculum Studies, 2016)
The focus on Canadian curriculum landscapes in this issue is imaginatively re-formed through playing with a composite digital artwork and a poem created from photographs and text taken from the current issue’s submissions. The metaphor of a personal métissage through time by weaving threads from JCACS’ first issue through to the current issue is used to describe the verdant terra of Canadian curriculum studies.